Cross-Media Narrative and Emotional Identity Mechanism of School Culture in Media Integration Environment. - Jia, Anmin (Journal of Environmental & Public Health, 2022)
Cross-media narrative of school culture is essentially different from emotional identity. We cannot just rely on students' rote learning to achieve this teaching goal, but we must let students gradually deepen their learning experience in the learning process. As a new narrative form in the context of media convergence, its narrative strategy from the perspective of media convergence culture can promote the industrialization of IP cultural resources, such as content production, marketing and dissemination, and derivatives development. This paper mainly studies the cross-media narrative and emotional identity of school education culture through wavelet transform algorithm. The research shows that the error rate of this paper is the lowest among the three methods, with the highest error rate of 46.8%, followed by the method of literature Sara 2018 with the highest error rate of 64.8%, and finally the method of literature Neate et al. 2017 with the highest error rate of 71.8%. It can be seen that this method is the most suitable for identifying the emotional characteristics of school education culture. Through wavelet transform, teachers can infiltrate the basic knowledge of Chinese into the cultivation of students' emotions in the teaching process, which is conducive to students' emotional edification, personality development, and self-motivation.